Occupational radiation exposure in anesthesia for hepatic chemoembolization: a prospective study - Jaramillo-Garzón, William; Andrade, Gustavo; Khoury, Helen J. (Colombian Journal of Anesthesiology, 2023)
Introduction: Anesthetists play an important role during interventional radiology procedures. Like the main operator, anesthetists may also be subject to significant radiation levels in the fluoroscopy suite. Due to its complexity, hepatic chemoembolization procedures demand high fluoroscopic times and digital subtraction angiography images, exposing patients and medical staff to high radiation doses. Objetive: To assess and quantify the radiation to which one anesthetist was exposed over the course of seven consecutive hepatic chemoembolization procedures, and compare it to the exposure received by the main operator. Methods: Medical staff dosimetry was evaluated during seven consecutive hepatic chemoembolization procedures conducted in a private hospital in Recife (Brazil), using thermoluminiscent dosimeters placed in regions of the head and torso. Results: For the seven procedures evaluated in this study, the anesthetist received, on average, absorbed doses to the glabella, left eyebrow, right eyebrow and effective dose of 142.4 ± 72 µSv, 117.3 ± 66 µSv, 137.8 ± 71 µSv and 12.4 ± 8.4 µSv, respectively. Conclusions: In some cases, ocular dose and effective dose received by the anesthetist may be 4 and 4.7 times greater, respectively, when compared to the main operator. According to the results of this study, the current occupational annual dose limit to the lens of the eye of 20 mSv can be exceeded with only two hepatic chemoembolization procedures per week if adequate radiation protection conditions are not guaranteed.